Influence of displacement damage induced by neutron irradiation on effective carrier density in 4H-SiC SBDs and MOSFETs. (25th February 2019) - Chao, Der-Sheng; Shih, Hua-Yu; Jiang, Jheng-Yi; Huang, Chih-Fang; Chiang, Ching-Yu; Ku, Ching-Shun; Yen, Cheng-Tyng; Lee, Lurng-Sheng; Hsu, Fu-Jen; Chu, Kuo-Ting; Hung, Chien-Chung; Lee, Chwan-Ying
Abstract: In this study, the fission neutron source and Co-60 gamma rays were employed to investigate the radiation effects on the electrical characteristics of the 4H-SiC SBDs and metal-oxide-semiconductor field-effect transistors (MOSFETs). The results indicated that SiC MOSFETs are more susceptible to gamma-ray irradiation than SiC Schottky barrier diodes (SBDs) due to the ionizing-produced charges trapped in the gate insulator. Compared to the ionizing effects caused by gamma rays, the neutron-induced displacement damage is more significant, since the defects originating from neutron irradiation would disturb the effective carrier density in SiC and lead to undesirable electrical deterioration and permanent failure of the SiC SBDs and MOSFETs.